The Subversion of the Meanings of Food Tropes in Salman Rushdie’s Novel “Midnight’s Children” - Radavičiūtė, Jūratė (Respectus Philologicus, 2022)
The article investigates the subversion of the meanings of food tropes in Salman Rushdie’s novel “Midnight’s Children”. The research is carried out within the theoretical framework of Postethnic Narrative Criticism, which postulates that historical and political contexts are relevant for understanding and interpreting the postethnic literary work; however, literature should not be perceived as an accurate representation of reality outside the world of fiction or interpreted as such. The article provides an analysis of the key connotations of the tropes in the description of Doctor Aziz and his family, emphasizing that food-related tropes are restricted to the private life of the characters discussed and are mainly associated with female characters. In portraying the Azizes’ children, the initial meanings of the tropes are subverted and undermined. The process of subversion is determined by societal changes which impact the main characters’ public and private lives.
Keywords: Rushdie; Midnight's Children; subversion; food tropes; posethnic literature